A Peningkatan Pendapatan Masyarakat Melalui Budidaya Lebah Madu Di Desa Tuva Kecamatan Gumbasa Kabupaten Sigi Sulawesi Tengah - Abdul Hapid (Jurnal Mitra Prima, 2023)
Non-Timber Forest Product (NTFP) is one of the forest resources that have a comparative advantage and are most in contact with the people living around the forest. One of the NTFPs that has been proven to have an impact on increasing the income of people living around the forest is honeybees. Honey beekeeping can provide direct benefits by utilizing products produced by honeybees such as honey, royal jelly, bee pollen, wax, adhesive (propolis), and honey poison. In addition, honeybee cultivation can provide indirect benefits, namely increasing plant productivity through a mutually beneficial symbiosis between plants and honeybees. The goal to be achieved in this service program is to help partner farmer group communities in Tuva Village, Gumbasa District, Sigi Regency to increase their income through optimal honeybee cultivation skills. The methods used to achieve goals and targets are forms of science and technology implementation such as counseling, training, and mentoring. The method used is persuasive-educative-communicative-participative. Counseling and training will include explaining: Honeybee Cultivation Techniques, techniques for making bee boxes, and how to harvest honey effectively. The results of the service show that the members of the farmer group are very interested in cultivating honeybees in their area. Honey beekeeping activities in Tuva Village can increase the income of farmer groups.